A Flux-Corrected Phase-Field Method for Surface Diffusion (Communications in Computational Physics, 2018)
Phase-field methods with a degenerate mobility have been widely used tosimulate surface diffusion motion. However, apart from the motion induced by surfacediffusion, adverse effects such as shrinkage, coarsening and false merging have beenobserved in the results obtained from the current phase-field methods, which largelyaffect the accuracy and numerical stability of these methods. In this paper, a flux-correctedphase-field method is proposed to improve the performance of phase-fieldmethods for simulating surface diffusion. The three effects were numerically studiedfor the proposed method and compared with those observed in the two existing methods,the original phase-field method and the profile-corrected phase-field method. Resultsshow that compared to the original phase-field method, the shrinkage effect in theprofile-corrected phase-field method has been significantly reduced. However, coarseningand false merging effects still present and can be significant in some cases. Theflux-corrected phase field performs the best in terms of eliminating the shrinkage andcoarsening effects. The false merging effect still exists when the diffuse regions of differentinterfaces overlap with each other. But it has been much reduced as comparedto that in the other two methods.